Immobilization of Iron on Carbon Nanospheres By TRIS-(1,10-Phenanthroline) Iron (II) Sulphate Complex for Supercapacitor Applications - Aashima (My University, 2019)
Uniform and mesoporous carbon nanospheres (CNS) have great applications in many areas of science like supercapacitor, catalyst, batteries and many more. This work describes immobilization of iron on surface of CNS by sonication method. Preformed CNS of average diameter of 470nm, prepared by hydrothermal method was used. A well-known organometalic compound, tris-(1,10-phenanthroline)-iron (II) sulphate was used for the immobilization purpose. All the materials were characterised using UV-Visible Spectroscopy, FTIR, SEM and BET surface area analyzer as applicable. Three different samples of CNS having varying percentage of iron were synthesized. The samples were further used in decolorisation of methylene blue dye by absorption in dark and degradation in UV light. The degradation decreased from 80% by bare CNS to 64% by Fe immobilized CNS but absorption of dye increased from 27% to 37.5% in dark. The Fe immobilized CNS were also demonstrated for super capacitor applications as electrode and Cdlvalue was best for CNS partially immobilized with Fe.
M.Sc Thesis of Aashima
Keywords: CNS; Methylene blue dye; Degradation; Supercapacitor; Immobilization; Sonication